Turkey’s Political Economy in the 21st Century
XXVI, 303 p. 40 illus., 19 illus. in color.
Keywords: This book shows the remarkable diversification in Turkey’s international political economy landscape in the 2000s: its domestic political-economy framework, instrumental alternatives and geographic outreach. It assesses both how an emerging economy like Turkey copes with domestic and external challenges and the question of how substantial Turkey’s recent rise in global politics really is. The volume also explains Turkey’s economic growth and political transformation in line with the changes occurring in world economics, from the Washington Consensus era to the current “mix” or “hybrid” era encompassing both the characteristics of the Post-Washington and Beijing Consensus eras. The contributors portray the complexity of Turkish politics and its fragilities at the political economy level. Emel Parlar Dal is Associate Professor at Marmara University’s Department of International Relations, Turkey. .